2014
DOI: 10.1002/chin.201426139
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Biological Evaluation of Some New 2,5‐Disubstituted 1,3,4‐Oxadiazoles from 3‐(Arylsulfonyl)propanehydrazides.

Abstract: are prepared and screened for their antimicrobial activities. (IIIa) and (IIIb) are the most active compounds. -(KUMAR, L. V.; NAIK, P. J.; NAVEEN, M.; CHANDRASEKHAR, T.; REDDY, A. B.; PENCHALAIAH, N.; SWAMY*, G. N.; Indian J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The carbon-NMR spectrum of (phozbt) was recorded in dimethyl sulfoxide solvent. The carbonyl carbon band displayed at (174.43) ppm; C 7 (Joshi et al, 2015).The two carbon atom (C 6 and C 5 ) of oxadiazole ring occurred at (164.55 and 157.64) ppm respectively (Kumar et al, 2014). The peaks observed at (133.62, 132.81, 130.53 and 128.09) ppm were correspondingly ascribed to aromatic benzo carbon of (C 8 , C 11 , C 10 and C 9 ) (Almajan et al, 2008).…”
Section: C-nmr Spectrum Of (Phozbt)mentioning
confidence: 97%
See 1 more Smart Citation
“…The carbon-NMR spectrum of (phozbt) was recorded in dimethyl sulfoxide solvent. The carbonyl carbon band displayed at (174.43) ppm; C 7 (Joshi et al, 2015).The two carbon atom (C 6 and C 5 ) of oxadiazole ring occurred at (164.55 and 157.64) ppm respectively (Kumar et al, 2014). The peaks observed at (133.62, 132.81, 130.53 and 128.09) ppm were correspondingly ascribed to aromatic benzo carbon of (C 8 , C 11 , C 10 and C 9 ) (Almajan et al, 2008).…”
Section: C-nmr Spectrum Of (Phozbt)mentioning
confidence: 97%
“…The dissaperance of the SH band at (2.5) ppm that remarked in (phoztH) ligand indicates the formation of the thioester (phobt) ligand (figure 1) (Husain and Ajmal, 2009) (Kumar et al, 2014). 10' Figure 1: 1 H-NMR spectrum of (phozbt) ligand…”
Section: Proton-nmr Spectrum Of (Phozbt)mentioning
confidence: 97%
“…Kumar et al [87] synthesized some new 2,5-disubstitued 1,3,4-oxadiazoles from (3-arylsulfonyl) propane hydrazides Maddela et al [88] reported ten new N'-subtituted-2-methylquinoline-3-carbohydrazide (38) and screened for in vitro antimicrobial and antioxidant activities. The results clearly revealed that all ten compounds possess in vitro antioxidant activity at the tested dose as compared to the standard drug, ascorbic acid as shown in Figure 11.…”
Section: Substituted Derivatives Of Hydrazidesmentioning
confidence: 99%
“…These are widely used as antimicrobial agents, antidiabetic agents, diuretics, anticonvulsants, antiretroviral and Hepatitis-C antiviral agents. Several researches revealed that the broad spectrum antimicrobial activity of sulfone containing heterocycles entities [2][3][4][5][6][7][8][9][10] Recently, Kudruavtsev et al [11] reported that the sulfone bearing pyrrolidine derivatives inhibits Staphylococcus aureus sortase SrtA isoform, irreversibly by modification of enzyme cys 184.…”
Section: Introductionmentioning
confidence: 99%
“…: 145.2 °C, IR (KBr, νmax, cm -1 ): 3321, 3265, 3028, 3002, 2995, 1789, 1636, 1622, 1518, 1221, 1180, 1082, 960, 882, 766; 1 H NMR (400 MHz, CDCl3) δ 12.58 (br s, 1H), 7.40 (m, 10H), 5.29 (d,J = 4.2 Hz,1H),5.19 (d,J = 4.2 Hz,1H),4.21 (q,J = 7.6 Hz,2H),3.58 (t,J = 8.2 Hz,2H),3.11 (t,J = 8.2 Hz,2H),1.29 (t,J = 7.8 Hz,3H) ppm; 13 C NMR (100 MHz, CDCl3) δ 171. 5,163.7,143.4,140.2,136.4,129.3,128.9,128.6,127.7,125.9,125.1,113.4,87.6,61.6,41.7,35.6,29.6,14.2 ppm;HRMS (ESI,m/z): 417.1249 calcd. for C22H22N2O3S (M+Na) found: 417.1247.…”
Section: Introductionmentioning
confidence: 99%